Development of Genially-based history learning media to increase learning interest of senior high school students - Putri, Henny Rosa; Setiawan, Risky; Ramadan, Syahri; Peng, Li-Hsun (Harmoni Sosial: Jurnal Pendidikan IPS, 2023)
This research aims to (1) produce Genially-based history learning media, (2) determine the feasibility of Genially-based history learning media, and (3) determine the effectiveness of Genially-based history learning media on student learning interest. This research is a Research and Development (R&D) study that uses the 4D development model. The research subjects were 74 students of class X SMA Negeri 1 Indralaya and SMA Negeri 1 Indralaya Utara using a pre-experiment model of one group pretest-posttest design. Data collection instruments included expert, teacher, and student assessment questionnaires and a questionnaire of student interest in Genially-based history learning media. Data analysis used paired sample t-test analysis. The results of this study are (1) a product in the form of Genially-based history learning media about Hindu and Buddhist Kingdoms in Indonesia, which contains elements of text, audio, images, video, animation, and games; (2) the average score obtained from material experts on Genially-based history learning media is 4.53 (very good), and the average score from media experts is 4.43 (very good). The average score of the history teacher is 4.57 (very good). Meanwhile, the results of the limited trial obtained an average score of 4.23 (very good), and the broad trial obtained a score of 4.41 (very good) so that the Genially-based history learning media is feasible to use; (3) the product developed by researchers is effective for increasing student interest in learning known from the results of the paired sample t-test which proves that the value of Asymp. Sig. (2-tailed) value of this study is 0.000, which is smaller than 0.05. This research contributes to improving the quality of education and student learning outcomes.